2011
DOI: 10.1063/1.3624890
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of charge transfer into the explicit polarization fragment method by grand canonical density functional theory

Abstract: Molecular fragmentation algorithms provide a powerful approach to extending electronic structure methods to very large systems. Here we present a method for including charge transfer between molecular fragments in the explicit polarization (X-Pol) fragment method for calculating potential energy surfaces. In the conventional X-Pol method, the total charge of each fragment is preserved, and charge transfer between fragments is not allowed. The description of charge transfer is made possible by treating each fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 90 publications
(98 reference statements)
0
25
0
Order By: Relevance
“…If the specific description of charge transfer effects is important for a given problem, the fragment partitions need to be assigned in such a way that the electron donor and acceptor groups are both included in the same fragment. Alternatively, resonance charge delocalization effects can be modeled by the multiconfigurational, generalized X-Pol (GX-Pol) theory highlighted recently [47, 53] or by using ensemble DFT [16]. Here, however, we tested the simpler approach in which charge transfer is only implicit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the specific description of charge transfer effects is important for a given problem, the fragment partitions need to be assigned in such a way that the electron donor and acceptor groups are both included in the same fragment. Alternatively, resonance charge delocalization effects can be modeled by the multiconfigurational, generalized X-Pol (GX-Pol) theory highlighted recently [47, 53] or by using ensemble DFT [16]. Here, however, we tested the simpler approach in which charge transfer is only implicit.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, one can treat all fragments by using the same method, or by mixing different electronic structure methods for different fragments (for example, MP2 for one fragment and DFT for all other fragments). Because a large system is partitioned into fragments, the X-Pol method can be made to scale well for fast calculations, and therefore, it can be used to establish a framework for the development of a next-generation force field [4] that goes beyond the conventional molecular mechanics by explicitly including a quantum mechanical treatment of electronic polarization and possibly charge transfer effects (which can be included, for example, by a recently proposed method [16] involving ensemble DFT). When X-Pol is used as a force field, we introduce a set of empirical terms to account for the missing exchange repulsion [17] and dispersion-like attractive, noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the GC-X-Pol to ten molecular complexes showed that the CT energy from this approach follows the trend of the BLW results. 394 Khaliullin et al reported a study on water dimer and other complexes using the absolutely localized molecular orbitals energy decomposition (ALMO-ED) scheme. 395 It was found that, unlike the polarization energy, the CT energy was sensitive to the water dimer orientation (flap angle).…”
Section: Accurate Representation Of the Electronic Chargementioning
confidence: 99%
“…The strict block localization of molecular orbitals within individual monomers in X-Pol does not allow charge delocalization between different fragments (unless one uses a grand canonical formulation, which is not employed here). 31 At distances longer than hydrogen bonding range, it is often a good approximation to neglect charge transfer, and interfragment electrostatic interactions can then be adequately described by the electrostatic embedding scheme 43–44 using the Coulomb potential (eq 5). However, at short interfragment distances where there is significant orbital overlap, one needs to take into account the energy component due to charge delocalization (sometimes also called charge transfer).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, at short interfragment distances where there is significant orbital overlap, one needs to take into account the energy component due to charge delocalization (sometimes also called charge transfer). 3031,61 In the present work, we account for charge transfer only empirically, in particular (in the spirit often used in molecular mechanics) 62 by modeling the charge delocalization energy with enhanced electrostatic polarization. Consequently, the electrostatic potential normalΦnormalEB(boldrxA) in eq 5 is recognized as an effective potential that mimics both long-range Coulomb (electrostatic) interactions and short-range charge delocalization contributions, and this can be achieved to some extent by optimizing the parameters in the EitalicABXD term (eq 7) and possibly the charge model 63 {qbB[ρitaliceleB]} (eq 5) to best reproduce hydrogen bonding interactions for a set of bimolecular complexes 38 (however such optimization is beyond the scope of the present article).…”
Section: Theoretical Backgroundmentioning
confidence: 99%